2016
DOI: 10.3390/md14120222
|View full text |Cite
|
Sign up to set email alerts
|

Marine Algae as a Potential Source for Anti-Obesity Agents

Abstract: Obesity is a major epidemic that poses a worldwide threat to human health, as it is also associated with metabolic syndrome, type 2 diabetes and cardiovascular disease. Therapeutic intervention through weight loss drugs, accompanied by diet and exercise, is one of the options for the treatment and management of obesity. However, the only approved anti-obesity drug currently available in the market is orlistat, a synthetic inhibitor of pancreatic lipase. Other anti-obesity drugs are still being evaluated at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
91
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(92 citation statements)
references
References 108 publications
0
91
0
1
Order By: Relevance
“…On the other hand, recent studies have discussed a variety of drugs from marine sources that promote anti-obesity effects such as Fucoxanthin from brown algae. In addition, a number of previous studies showed that the positive effect on anti-obesity of diets contains extracts from brown seaweeds [56]. Those studies found that the diets supplemented with the extracts from seaweeds have an inhibitory effect on lipogenesis in adipocytes, decrease in total cholesterol and triacylglycerol levels as well as blood glucose and insulin levels and especially in reducing the body weight [56].…”
Section: As a Potential Functional Food For Anti-obesity And Other Mementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, recent studies have discussed a variety of drugs from marine sources that promote anti-obesity effects such as Fucoxanthin from brown algae. In addition, a number of previous studies showed that the positive effect on anti-obesity of diets contains extracts from brown seaweeds [56]. Those studies found that the diets supplemented with the extracts from seaweeds have an inhibitory effect on lipogenesis in adipocytes, decrease in total cholesterol and triacylglycerol levels as well as blood glucose and insulin levels and especially in reducing the body weight [56].…”
Section: As a Potential Functional Food For Anti-obesity And Other Mementioning
confidence: 99%
“…In addition, a number of previous studies showed that the positive effect on anti-obesity of diets contains extracts from brown seaweeds [56]. Those studies found that the diets supplemented with the extracts from seaweeds have an inhibitory effect on lipogenesis in adipocytes, decrease in total cholesterol and triacylglycerol levels as well as blood glucose and insulin levels and especially in reducing the body weight [56]. Since AOS and their derivatives are water-soluble, non-toxic and no sideeffect, they may be beneficial biomaterials in various metabolic disorders such as obesity and diabetes.…”
Section: As a Potential Functional Food For Anti-obesity And Other Mementioning
confidence: 99%
“…Regarding specific benefits on human health, seaweeds have demonstrated to exert preventive effects against several non-transmissible diseases such as cardiovascular diseases [11,12], antihypertensive [13], anti-obesity effects [14] and anti-diabetic effects [15,16], anti-cancer [17,18] or antioxidant activities [19].…”
Section: Introductionmentioning
confidence: 99%
“…The potential anti-obesity activity derived from seaweeds consumption may involve a large variety of mechanisms and alterations in lipid metabolism, suppression of inflammation, suppression of adipocyte differentiation and delay in gastric emptying [14]. Between then, an important anti-obesity activity of seaweeds is the inhibition of peroxisome proliferator-activated receptor γ (PPARγ) expression and activation of the adenosine monophosphate-activated protein kinase (AMPK) phosphorylation [13].…”
Section: Introductionmentioning
confidence: 99%
“…The α-amylase and α-glucosidase inhibition properties of solvent extracts of several red, brown and green macro algae have been reported by numerous authors from elsewhere (Chu & Phang, 2016;Heo, Park, Lee, & Jeon, 2005;Kim et al, 2014;Lordan et al, 2013;Pai-An, Shih-Yung, Yu-Lan, YiKuan, & Zwe-Ling, 2013;Schultz Moreira et al, 2014;Xindi et al, 2016;Yuan & Walsh, 2006). In addition, the antihypertensive, Angiotensinconverting enzyme (ACE) inhibiting properties and antioxidant activities of seaweed protein hydrolysates and peptides has been reported in the previous studies (Beaulieu, Sirois, & Tamigneaux, 2016;Ko et al, 2012;Qu et al, 2015;Qu et al, 2010;.…”
Section: Introductionmentioning
confidence: 99%